Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/s2213-8587(15)00040-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate and albuminuria for prediction of cardiovascular outcomes: a collaborative meta-analysis of individual participant data

Abstract: BackgroundThe utility of estimated glomerular filtration rate (eGFR) and albuminuria for cardiovascular prediction is controversial.MethodsWe meta-analyzed individual-level data from 24 cohorts (with a median follow-up time longer than 4 years, varying from 4.2 to 19.0 years) in the Chronic Kidney Disease Prognosis Consortium (637,315 participants without a history of cardiovascular disease) and assessed C-statistic difference and reclassification improvement for cardiovascular mortality and fatal and non-fata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
510
1
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 676 publications
(550 citation statements)
references
References 36 publications
28
510
1
11
Order By: Relevance
“…This finding has direct clinical implications for CV risk stratification and intensive therapeutic targeting of the subpopulations at the highest risk for future CV events and mortality. For example, as pointed out in previous studies (34), full assessment of kidney function, including not only eGFR but also, urine albumin excretion, is likely to be beneficial for complete CV risk assessment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding has direct clinical implications for CV risk stratification and intensive therapeutic targeting of the subpopulations at the highest risk for future CV events and mortality. For example, as pointed out in previous studies (34), full assessment of kidney function, including not only eGFR but also, urine albumin excretion, is likely to be beneficial for complete CV risk assessment.…”
Section: Discussionmentioning
confidence: 91%
“…Previous work in largely white populations has shown that CKD contributes significantly to CV risk stratification (34) and that the combination of diabetes and CKD is associated with comparable rates of incident myocardial infarction to preexisting CHD (35). Given our focus on incident outcomes (stroke and CHD), prevalent stroke (or CHD) could not be included in our assessment of risk factor for incident stroke (or CHD).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17] . Renal function can be roughly assessed by serum creatinine level but more accurately evaluated from estimated glomerular filtration rate (eGFR), which is usually automatically calculated in a clinical setting, based on serum creatinine and basic demographic findings.…”
Section: Discussion:-mentioning
confidence: 99%
“…Underlying mechanisms are multifactorial, but cardiac overload, vascular calcification, and arterial stiffness in reduced glomerular filtration rate (GFR) can cause ventricular‐arterial coupling mismatch 1, 2. In addition, albuminuria, the other important marker for defining and staging CKD,3 reflects endothelial function4 and low‐grade inflammation5 and is strongly associated with CVD risk 6…”
mentioning
confidence: 99%